Changes in excitability and GABAergic neuronal activity of the primary somatosensory cortex after motor learning - Pham, Manh Van; Saito, Kei; Miyaguchi, Shota; Watanabe, Hiraku; Ikarashi, Hitomi; Nagasaka, Kazuaki; Yokota, Hirotake; Kojima, Sho; Inukai, Yasuto; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Neuroscience, 2022)
Introduction: It is widely known that motor learning changes the excitability of the primary motor cortex. More recently, it has been shown that the primary somatosensory cortex (S1) also plays an important role in motor learning, but the details have not been fully examined. Therefore, we investigated how motor skill training affects somatosensory evoked potential (SEP) in 30 neurologically healthy subjects. Methods: Somatosensory evoked potential N20/P25_component and N20/P25 SEP paired-pulse depression (SEP-PPD) were assessed before and immediately after complex or simple visuomotor tasks. Results: Motor learning was induced more efficiently by the complex visuomotor task than by the simple visuomotor task. Both the N20/P25 SEP amplitude and N20/P25 SEP-PPD increased significantly immediately after the complex visuomotor task, but not after the simple visuomotor task. Furthermore, a higher increase in motor learning efficiency was significantly associated with a higher N20/P25 SEP amplitude increase in the complex visuomotor task. Conclusion: These results suggest that motor learning modulated primary somatosensory cortex excitability.